Vaginismus: An Approach from biology to psychological aspect - Bintang Arroyantri Prananjaya; Syarifah Aini; Jiann Lin Loo; Diyaz Syauki Ikhsan; Puji Rizki Suryani; Alessandro Syafei Rashid (Faculty of Medicine, Universitas Airlangga, 2023)
Background: The prevalence of vaginismus ranges from 1-6%, and the ratio becomes 5%-17% in clinical setting, although it varies widely worldwide. The main cause of vaginismus is not known, but is often considered multifactorial. This paper aims to describe the factors that contribute to vaginismus. Case: A 26 years old, married woman, health practitioner presented with the complaint of not being able to have sexual intercourse. About 1 month ago, since marriage, the patient was unable to have sexual intercourse with her husband. The patient feels guilty and anxious because of the inability to please her husband. The patient's father was very dominant and was a